Acceptable durability of split inner table graft for the reconstruction of a bone defect in pterional craniotomies: a case series - Kweon, Gi-Young; Park, Jaechan; Son, Wonsoo (Frontiers in Surgery, 2023)
Objective During a pterional craniotomy, the bone defect was reconstructed by a surgical technique using an autogenous bone graft instead of commercially available alloplastic materials. The technical feasibility, durability of the grafted bone, and cosmetic outcome were all evaluated. Methods After a pterional craniotomy was performed, the bone defect at the frontobasal burr hole and drilled sphenoid wing was reconstructed using an autogenous split inner table graft (1 cm × 2 cm) harvested from the craniotomy bone flap. Results The bone reconstruction technique was successfully performed on nine patients with intracranial aneurysms. After 12–19 months from the surgery, a volumetry study using three-dimensional skull images reconstructed from computed tomography angiography showed a minimal decrease in the area of the split inner table graft due to bone resorption in six patients, which ranged from 5.7% to 14.8%. In the other three patients, the bone resorption was more substantial, ranging from 21.2% to 27.5%. However, in the three latter cases, the resorption was mainly limited to the posterior part of the split inner table graft covered by the temporalis muscle and did not affect the cosmetic outcomes. The resultant cosmetic outcomes for the nine patients were all favorable, with only a slight or no anterior temporal hollow. Conclusion The proposed surgical technique using a split inner table graft harvested from the craniotomy bone flap seems viable for reconstructing the bone defect at the frontobasal burr hole and drilled sphenoid wing after a pterional craniotomy.